2003
DOI: 10.1029/2002rs002758
|View full text |Cite
|
Sign up to set email alerts
|

Radio wave propagation through vegetation: Factors influencing signal attenuation

Abstract: [1] The paper describes an extensive wideband channel sounding measurement campaign to investigate signal propagation through vegetation. The measurements have been conducted at three frequencies (1.3, 2 and 11.6 GHz) at sites with different measurement geometries and tree species. The data have been used to evaluate current narrowband empirical vegetation attenuation models and study the prevailing propagation mechanisms. Evaluation of the modified exponential decay (MED), maximum attenuation (MA) and nonzero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…This effect is expected as many studies have reported the decrease of the attenuation of trees without foliage e.g. [6], [7] and [8]…”
Section: Measurement Periodmentioning
confidence: 79%
See 1 more Smart Citation
“…This effect is expected as many studies have reported the decrease of the attenuation of trees without foliage e.g. [6], [7] and [8]…”
Section: Measurement Periodmentioning
confidence: 79%
“…There are many studies e.g., [6], [7] and [8], which have reported the seasonal effect i.e., the increase in the attenuation of trees inleaf compared with the out-of-leaf state.…”
Section: Environmental Impacts On Signal Propagationmentioning
confidence: 99%
“…Different parameter values have been proposed depending on the frequency, foliage type, and propagation mechanisms etc. The advantage of the exponential decay model lies in its simplicity, but it has a major drawback that it does not take into account the measurement geometry as indicated by Savage et al in [19].…”
Section: Foliage Loss Model For the Horizontal Pathmentioning
confidence: 99%
“…From these comparative works [13,[17][18][19], it can be found that taking into the consideration of the measurement geometry, tree species, leaf shape and foliated state, the NZG model is the better method of the foliage loss prediction at the microwave and millimeter wave as compared to other models in Table 1. However, as pointed out by Savage et al [19], the values obtained at one site for the NZG model may not be used to predict attenuation at another because they encompass propagation anomalies that may not exist at both sites.…”
Section: Foliage Loss Model For the Horizontal Pathmentioning
confidence: 99%
See 1 more Smart Citation